Primary thyroid lymphoma: A case report and review of the literature. (January 2017) - Peixoto, Rita; Correia Pinto, João; Soares, Virgínia; Koch, Pedro; Taveira Gomes, António
Abstract: Introduction: A rapidly enlarging mass of the anterior compartment of the neck with compressive symptoms may represent, among other diagnosis, a neoplasm of the thyroid gland. Presentation of case: We describe the case of a 59-year-old woman referred to the endocrine surgical unit because of compressive cervical symptoms for 3 months. The cervical ultrasound revealed a sub-sternal goiter with heterogeneous echo structure and the fine-needle aspirating cytology was inconclusive. Given the large impact of symptoms on life quality, she was submitted to a total thyroidectomy. Histological examination of the surgical specimen revealed the presence of a Diffuse Large B Cell Lymphoma of the thyroid. Discussion: Primary thyroid lymphomas are rare and there are few randomized studies for diagnostic and therapeutic guidance. New immunohistochemical and molecular techniques have improved the diagnostic accuracy with corebiopsy limiting the role of surgery. The treatment should first include the control of local disease with radiotherapy and/or surgery combined with chemotherapy to control obscure or disseminated disease. Palliative surgery may be needed to relieve airway compression symptoms. Under these circumstances, surgery should be performed by a specialized surgeon to decrease the associated morbidity. The prognosis of patients depends on the histological classification of the tumor and the stage of the disease. Conclusion: Due to the rarity of the disease, each case must be evaluated and treated individually, since there is not a consensual therapeutic approach. Highlights: Primary thyroid lymphomas are very rare. New immunohistochemical and molecular techniques have improved the diagnostic accuracy with corebiopsy limiting surgery. Surgery has a small role in PTL and when needed it should be performed by a specialized surgeon to decrease morbidity.